A study on factor that influence customer satisfaction toward quality services provided by Tabung Haji, Tanjong Karang, Selangor / Siti Zarina Mohamad Amin - Mohamad Amin, Siti Zarina (Faculty of Administration Science and Policy Studies, 2004)
The Pilgrims Fund Board (Lembaga Tabung Haji) was established from the establishment of Pilgrims Fund Corporation in November 1962 and commenced operation on September 30,1963 with the main objective of providing quality product and services to the customers. TH Tanjong Karang is one of the TH's branch established in order to facilitate the resident of Tanjong Karang to get the services provided by TH The main services provided by TH are saving and withdrawing and also hajj registration.